ANALISIS KESALAHAN KONSEP MATEMATIKA SISWA SMP DALAM MENYELESAIKAN SOAL MATERI BANGUN RUANG SISI DATAR - Wulan Fitri Kania; M. Ghiyats Ristiana (IKIP Siliwangi, 2021)
This research was conducted to analyze the student's mathematical concept errors when solving problems of the polygon. The method used is descriptive with a qualitative approach to describe the results of the analysis of the errors made by students. The research subjects were students of SMP class IX in one of the schools in West Bandung and totaled 30 people. The research instrument is 6 descriptive questions. The results showed that students' errors in numbers 1 and 2 were in a low category, questions numbered 3 and 4 were in the medium category, while questions numbered 5 and 6 were in the high category. Conceptual errors made by students are (1) errors in determining the formula to be used; (2) formula writing error; (3) errors in determining and substituting data into variables; (4) errors in determining the relationship between BRSD concepts. Factors that cause: less thorough in understanding the problem, wrong in analyzing the problem, error in performing calculation operations, not re-checking the answers. With these results, the solution that can be given is that teachers can better teach concepts by utilizing approaches, methods, strategies, and learning media that are tailored to the material and needs of students.